LEARNING STYLES USED AND ENGLISH PROFICIENCY OF THE STUDENTS OF ENGLISH EDUCATION STUDY PROGRAM FACULTY OF TEACHER TRAINING AND EDUCATION SRIWIJAYA UNIVERSITY - Hariswan Putera Jaya (HOLISTICS, 2019)
Abstract: This study aimed to find out the general description of learning styles, types of learning styles, and English proficiency of students of English Language Education Program,Faculty of Teacher Training and Education (FKIP),Sriwijaya University and to find out whether there was a correlation between their learning styles and their English proficiency in general. The population of this study was the 3rd, 5th and 7th semester students of Palembang and Inderalaya campuses. The results show that in general the learning style of the students was dominated by verbal learning style with the percentage of 46.3%followed by social, logical, auditory, solitary, visual, and physical learning styles with the percentage of 18%, 9.8%, 9.4%, 9%, 5.7%, and 1.6% respectively. In general, the students’ English proficiency was still at the elementary level(59%), low intermediate level(30.7%), intermediate level(7%), and advanced level(3.3%). There was no positive and significant correlation between students’ learning styles and their English proficiency.